Analisis Kinerja dan Keamanan Protokol PPTP dan L2TP/IPSec VPN pada Jaringan MikroTik - M. Khofikur R.A; Eka Putra, Fauzan Prasetyo; Ridho G, Moh. Wahid; Huda, Valentino (Infotek: Jurnal Informatika dan Teknologi, 2025)
Virtual Private Network (VPN) has become a critical solution for ensuring secure communication over public networks. This research conducts a comprehensive analysis of the performance and security of two major VPN protocols: Point-to-Point Tunneling Protocol (PPTP) and Layer 2 Tunneling Protocol with Internet Protocol Security (L2TP/IPSec) implemented on MikroTik devices. The research methodology uses an experimental approach by testing throughput, latency, packet loss, and CPU utilization in various network scenarios. The results show that PPTP provides higher throughput with minimal overhead, but has significant weaknesses in security aspects. Conversely, L2TP/IPSec offers superior security levels with strong encryption, although it results in higher latency and lower throughput. These findings provide important insights for network administrators in choosing VPN protocols that suit organizational needs, considering the trade-off between performance and security